Innovation In Waste Cooking Oil, Coconut, And Rice-Based Products Through Outreach Activities In Nagari Cupak - Wellyalina Wellyalina; Eddwina Aidila Fitria; Wawan Sumarno; Muhammad Faruqi Aidi; Hannisha Nanda Gussry (Andalasian International Journal of Social and Entrepreneurial Development, 2026)
Nagari Cupak in Solok Regency possesses significant local potential, particularly in coconut and Solok rice commodities; however, their use has remained limited to household consumption and raw material sales. In addition, waste cooking oil produced by households and small businesses is often unmanaged, posing environmental risks. This community engagement program aimed to enhance the skills of PKK women in utilizing local resources and converting household waste into value-added products. The activities included the delivery of materials on producing traditional coconut cooking oil and Virgin Coconut Oil (VCO), followed by hands-on workshops on making waste-cooking-oil soap and rice-based solid soap. A participatory approach was implemented through lectures, discussions, and guided practice. The results show that participants gained an improved understanding of coconut oil processing and were able to independently produce waste-oil soap and rice soap with acceptable texture and aroma. Challenges encountered included limited equipment for VCO practice and difficulties during soap molding. Overall, the program successfully increased community knowledge, technical skills, and awareness of local resource utilization while opening opportunities for small-scale entrepreneurship based on simple, locally sourced products.